Spontaneous strategy use in children with autism spectrum disorder: the roles of metamemory and language skills - Bebko, James M.; Rhee, Thomas; McMorris, Carly A.; Ncube, Busisiwe L. (Frontiers in Psychology, 2015)
Metamemory, or beliefs about one’s own memory capabilities, knowing what you know, and don’t know, has frequently been linked to the spontaneous use of rehearsal strategies in typically developing children. However, limited research has investigated mnemonic strategy use, metamemory, or the relationship between these two cognitive processes in children with autism spectrum disorders (ASDs). The current study examined the relative strength of metamemory knowledge and language skills as predictors of rehearsal use and memory performance in individuals with ASD. Twenty-one children with ASD and 21 children in a combined comparison group were matched on chronological and verbal mental age. Over two sessions, participants completed a serial recall task, a language measure, and a metamemory questionnaire. Children were classified as rehearsers/non-rehearsers based on behavioral observations and/or verbal reports of strategy use. As expected the comparison group had a significantly higher proportion of rehearsers than the ASD group. However, spontaneous rehearsers performed significantly better on the serial recall task than non-rehearsers, regardless of group membership. Children in the comparison group had a higher mean total score on the metamemory questionnaire than the ASD group. However, when examined by rehearsal use, participants classified as rehearsers, regardless of diagnostic group, scored significantly higher on the metamemory questionnaire than non-rehearsers. Finally, across groups, hierarchical regression analyses identified both metamemory and language proficiency as significant predictors of rehearsal strategy use. The fact that the predictors showed the same relationship across groups implies that metamemory and language proficiency, while separate entities, are both fundamental underlying skills contributing to the emergence of rehearsal strategies, and that the results are likely generalizable to other populations with developmental challenges.